PEMILU DAN KORUPSI : DILEMA KONSTESTASI CALEG MANTAN NAPI KORUPSI PADA PILEG 2019 - Sadeadema, Valentina Mariama (Faculty of Social and Political Science Universitas Brawijaya, 2019)
This article discusses the contestation dilemma of former legislative candidates for corruption in the 2019 legislative elections. The main focus is on the attraction of interests that occur between political parties and electoral institutions (KPU) in nominating former corruption prisoners in the 2019 legislative election. The method used is literature studies through the approach of the political party recruitment function. At present there are thirty-eight names of legislative candidates who have entered the list of Permanent Candidates (DCT) in the 2019 legislative elections. There is a long process and political interest that occurs followed by the submission of a Judicial Review to the Supreme Court. The results of this journal writing formulate that the factor behind the nomination of ex-corruptors as candidates is the recruitment of partisanship political parties who tend to uphold cadre loyalty to the party, followed by a legal regulation stating that the nomination of ex-corruptors does match with law No. 7 about Elections. Meanwhile, the KPU's rejection of the former corruptor candidates is the KPU's professional stakes to create clean elections by building the integrity of the legislative candidates and candidates.